The Role of Professional Learning Communities in Improving the Quality of Education in Primary Schools from the point of view of male and female teachers of primary schools in the cities of Dammam and Jubail, in the Kingdom of Saudi Arabia - Al-Otaibi, Anoud Ayedh (Journal of Educational and Psychological Sciences, 2022)
The objective of the study is to reveal the role of professional learning communities in improving the quality of education in primary schools. The researcher used the descriptive survey approach to achieve the objective of the study. The tool of the study was a questionnaire consisted of 19 sentences distributed to five dimensions that was applied to a random sample of (335) primary school teachers in the cities of Dammam and Jubail. The results showed that the role of professional learning communities in improving the quality of education in primary schools came with an arithmetic average of (3.63 out of 5), with a (large) role. At the level of the dimensions, the dimension of improving teaching methods came with the highest arithmetic average of (3.75), followed by the dimension of teachers’ professional practices with an arithmetic average of (3.75), then the dimension of school administration with an arithmetic average of (3.69), then in the fourth place the dimension of improving academic achievement with an arithmetic average of (3.52), where they all came with a (large) role and in the last place the dimension of school environment with an arithmetic average of (3.39) and with a (medium) role. There are statistically significant differences between the responses of the sample of the study due to the variable of gender in all the dimensions in favor of female teachers. There are no statistically significant differences between the responses of the study sample due to the variables of years of experience and academic qualification. Based on the results, the researcher recommended conducting training courses for teachers, developing their performance, enhancing participative leadership and providing educational means and modern technologies, as well as further supplementary studies on the subject.
Keywords: The role; Professional learning communities; Quality of education; Primary schools; Teachers' point of view; the cities of Dammam and Jubail